Effect of accelerated high-fluence riboflavin and rose bengal-mediated corneal cross-linking on resistance to enzymatic digestion - Nikki L. Hafezi; M. Enes Aydemir; Nan-Ji Lu; Emilio A. Torres-Netto; Mark Hillen; Carina Koppen (BMC Ophthalmology, 2024)
Abstract Purpose This study evaluated the effect of high-fluence accelerated corneal cross-linking on the resistance to enzymatic digestion, assessing two chromophore/light combinations: riboflavin/UV-A light (RF/UV-A) and rose bengal/green light (RB/green). Methods Freshly prepared ex-vivo porcine corneas (n = 189) were divided into 8 groups groups. Group A corneas were unirradiated controls without chromophore soaking (A0), or soaked with riboflavin (A1) or rose bengal (A2). Group B corneas underwent accelerated epi-off RF/UV-A CXL at fluences of 5.4 J/cm² (B1), 10 J/cm² (B2), or 15 J/cm² (B3). Group C corneas underwent accelerated epi-off RB/green CXL at fluences of either 10 J/cm² (C1) or 15 J/cm² (C2). Following CXL, all corneas were digested in 0.3% collagenase-A solution, and the time until complete dissolution was measured. Results Non-irradiated controls exposed to RF and RB enhanced corneal resistance to collagenase digestion, with RB having a stronger effect than RF. RF/UV-A-treated corneas showed significantly increased digestion resistance with increasing fluence levels. RB/green-treated corneas displayed enhanced digestion resistance with each increase in fluence up to 10 J/cm²; a 15 J/cm² fluence yielded similar digestion resistance times to a 10 J/cm² fluence, suggesting a plateau effect in accelerated RB/green CXL protocols. Conclusions When compared to standard-fluence treatments, high-fluence accelerated epi-off CXL using both riboflavin and rose bengal significantly increases resistance to enzymatic digestion. The optimal settings for clinical protocols might be 15 J/cm² (30 mW/cm² for 8 min 20 s) for RF/UV-A and 10 J/cm² (15 mW/cm² for 11 min 7 s) for RB/Green Light.